JUVENILE JUSTICE SYSTEM THROUGH DIVERSION AND RESTORATIVE JUSTICE POLICY - Dyah Listyarini (Fakultas Hukum, Universitas Diponegoro, 2017)
Indonesia as a state of law has ratified several international human rights instruments, especially the Convention on the Rights of the Child, in which the state should ensure the protection, respect, fulfillment, promotion, and enforcement of children's rights. In fact, many children have been treated unjustly in the fulfillment of their rights when conflicting with the law. Methods of legal protection of the rights of children conflicting with the law are based on the provision that “every child has the right to survive, grow and develop as well as the right to protection from violence and discrimination”. Other ways to protect children’s rights may also include the policy that children conflicting with the law should be treated humanely in accordance with their dignity and rights; special personnel should be provided for their companion and counseling; sanctions should be appropriated for the best interests of the children; and special facilities and infrastructure for children should be equally provided. This means that appropriate sanctions should hence be supported through the process of resolving cases using the principle of “diverse and restorative justice The concept of diverse and restorative justice can be applied to the crime of under 7th-year punishments and non-repeated crime. Methods for handling children who have conflicts with the law have hitherto emphasized on normative juridical processes such as investigation, prosecution, and examination of the case by the judge (in court). The processes, however, have not guidelines or technical manuals for law enforcement officers to implement the non-litigation settlement for children cases